Renewable energy sources for buildings. (TM (Chartered Institution of Building Services Engineers) ;, 2006)
This guidance has been produced as part of the CIBSE's response to a growing need to reduce carbon emissions from buildings. Several renewable energy technologies can be successfully integrated into buildings and developments if they are considered in the early stages of the planning and design process. This document gives guidance to developers, planners, designers and building owners to enable them to consider integrated renewable energy systems at this early stage. The guidance helps to identify the most appropriate low or zero carbon (LZC) energy solutions for buildings and/or developments based on users' requirements. It should be used at the early stages of a project, before factors such as orientation, building form, numbers of storeys, heating and ventilation strategy etc. have been established. It will be particularly helpful for projects which are required to carry out an assessment of the options for integrated renewable supply or are subject to explicit requirements set in Unitary Development Plans. --